Development of FinTech business in Lithuania: driving factors and future scenarios - Taujanskaitė, Kamilė; Kuizinaitė, Jurgita (Business, Management and Economics Engineering, 2022)
Purpose – the research aims to find out the main factors that determine the change in the number of FinTech companies in Lithuania and predict the future development of this sector. Research object: FinTech business sector, described as the number of FinTech companies.Research methodology – scientific literature analysis and generalisation, comparative analysis, statistical data collection and systematisation, correlation-regression analysis, scenario method for forecasting.Findings – the main factors that may determine the growth of the number of FinTech companies in Lithuania were identified and several development scenarios of the segment forecasted. The first part analyses related scientific investigations and FinTech's impact on the financial system as a whole. In the empirical part, a correlation and regression analysis of the factors that may determine the change of a number of FinTech companies was performed and ten main factors  identified. The possible evolution of the number of FinTech companies until 2024 under 5 scenarios has been predicted.Research limitations – the statistical information used in this research comes from different databases and different sources and may not always be free from certain discrepancies.Practical implications – the obtained results may be of interest for researchers who examine this issue and the Central Bank of Lithuania, performing surveillance of the financial market. The forecast under various scenarios of the economic situation enables the estimation of the impact the FinTech business may have and can be useful for the Ministry of Finance involved in strategic planning.Originality/Value – an attempt was made to fill in the scientific literature gaps and find out what factors influence the most FinTech sector development in Lithuania and how this sector might grow in the future.